2014
DOI: 10.1155/2014/142504
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Virtual Touch Tissue Quantification for Breast Lesions with Different Size

Abstract: Purpose. To evaluate diagnostic value of the virtual touch tissue quantification (VTTQ) for breast lesions with different sizes. Materials and Methods. Patients with 206 breast lesions were categorized into three groups according to lesion size (<10 mm, 10–20 mm, and >20 mm). Breast lesions were examined by conventional ultrasound and VTTQ, and shear wave velocity (SWV) of each lesion and adjacent normal breast tissue were measured. Diagnoses were confirmed by pathological examination after surgery. The receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 23 publications
2
10
0
1
Order By: Relevance
“…A cutoff value of 30.2 kPa with 41.9% sensitivity and 100% specificity for differentiation of benign from malignant lesions using real‐time shear wave elastography was previously reported 9 . Our cutoff value of 4.645 m/s was similar to 4.22 m/s for diagnosis of benign and malignant breast lesions 5 . Tourasse et al 10 found that stiffness measurements were significantly different between healthy and metastatic lymph nodes.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A cutoff value of 30.2 kPa with 41.9% sensitivity and 100% specificity for differentiation of benign from malignant lesions using real‐time shear wave elastography was previously reported 9 . Our cutoff value of 4.645 m/s was similar to 4.22 m/s for diagnosis of benign and malignant breast lesions 5 . Tourasse et al 10 found that stiffness measurements were significantly different between healthy and metastatic lymph nodes.…”
Section: Discussionsupporting
confidence: 76%
“…Virtual Touch tissue quantification (VTQ; Siemens Medical Solutions, Erlangen, Germany) enables determination of the shear wave velocity (SWV; meters per second) in tissues, which provides a quantitative measure of tissue stiffness 1 . Recently, VTQ has been used to assist in the diagnosis of breast masses, thyroid nodules, and chronic kidney disease 2 5 . However, to our knowledge, few studies of metastatic lymph nodes detected by VTQ have been published 6 .…”
mentioning
confidence: 99%
“…It is well known that malignant masses are usually stiffer than benign masses [ 26 – 29 ], for this reason, different SWE methods have been used to differentiate between benign and malignant masses in different organs. SuperSonic Imagine (SSI) [ 22 , 30 ] and shear wave imaging using Acoustic Radiation Force Impulse (ARFI) [ 31 , 32 ] are two of the most well-known SWE techniques. The advantages of these techniques in the differentiation of breast masses have been well studied [ 31 , 33 39 ], but few studies have investigated the effect of breast calcifications on SWE [ 40 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The measured shear wave speeds are used to calculate the stiffness properties of the tissue [ 21 ]. The diagnostic value of shear wave imaging using ARFI for characterization of B-mode detected breast lesions has been studied [ 23 , 24 , 25 ]. The push method used in SSI relies on generating a supersonic regime moving-source generating shear waves in the tissue using a conventional transducer.…”
Section: Introductionmentioning
confidence: 99%